IDENTIFICATION OF INDONESIAN ISLAMIC BANKS’ STAKEHOLDERS - Jahja, Adi Susilo; Sri Ramalu, Subramaniam A/L; Razimi, Mohd. Shahril Ahmad (JEBIM Prima, 2021)
Indonesian Islamic banks should strengthen their legitimacy in the eyes of stakeholders. For this reason, they must satisfy the stakeholders' expectations. Consequently, stakeholder identification is crucial. Previous studies have classified stakeholders of Indonesian Islamic banks into seven types. However, with the increase in the number of Islamic banks and the recent development in the Indonesian banking industry, such classification is needed to be reviewed. This study aims to identify the stakeholders of Indonesian Islamic banks as perceived by these banks. This research method is qualitative descriptive, using secondary data. Data is processed using content analysis. This study advanced knowledge about the types of stakeholders of Indonesian Islamic banks.